The effect of non-AIDS-defining cancers on people living with HIV. Issue 6 (June 2021) - Chiao, Elizabeth Y; Coghill, Anna; Kizub, Darya; Fink, Valeria; Ndlovu, Ntokozo; Mazul, Angela; Sigel, Keith
Summary: Non-AIDS-defining cancers are a growing source of morbidity for people with HIV globally. Although people living with HIV have a disproportionately increased risk of developing virally mediated cancers, cancer burden for common non-AIDS-defining cancers that are not virally associated and are linked to ageing, such as prostate cancer, is becoming higher than for virally mediated cancers. Ageing, behavioural, and HIV-specific factors drive the incidence and affect the outcomes of non-AIDS-defining cancers, presenting different challenges for addressing global morbidity and mortality from non-AIDS-defining cancer. Although large population-based studies have shown that people living with HIV with non-AIDS-defining cancers have poorer cancer outcomes than do people without HIV, current guidelines emphasise that people living with HIV with non-AIDS-defining cancers should receive standard, guideline-based treatment, and infectious disease and oncology providers should work closely to address potential drug interactions between antiretroviral therapy and antineoplastic treatment. Most trials target preventive measures focusing on non-AIDS-defining cancers. However, treatment trials for the optimal management of people living with HIV and non-AIDS-defining cancer, including interventions such as immunotherapies, are needed to improve non-AIDS-defining cancer outcomes.